Encyclopedia of Indian Knowledge Systems: A Gift to the World (Mythological Literatures and Social Progress Vol - 2) - Purohit, Vishnudut (New Delhi: Oxford Book Company, 2025)
Encyclopaedia of Indian Knowledge Systems: A Gift to the World provides an in-depth exploration of ancient, medieval, and contemporary knowledge systems, spanning a diverse range of disciplines such as Ayurveda, Yoga, Vedanta, astronomy, mathematics, architecture, linguistics, and the arts. It emphasises how Indian traditions are integrative, combining philosophy, science, and art to produce a comprehensive view of the cosmos. In addition to highlighting the historical significance of India's intellectual accomplishments, the encyclopedia's thoroughly researched content also looks at their applicability in the contemporary world. It highlights India's position as a leader in the spread of knowledge while charting the development of concepts and methods that have influenced viewpoints around the world. The encyclopaedia strikes a mix between academic rigour and readability, making it a priceless tool for scholars, students, and general readers. The encyclopaedia also celebrates India's intellectual and cultural diversity with the goal of preserving and advancing this rich heritage for next generations. It pushes readers to recognise the enduring value of Indian customs and how they may be applied to today's problems. Bridging the past and present, this book honours the timeless essence of Indian knowledge systems while providing insights that spur creativity and cross-cultural understanding. It is a wonderful gift to the world.
Keywords: Puranas; Vedic Civilization; Vedic Mathematics; Ancient Indian Medical System; Astronomy (Jyotisha); Metallurgy and Engineering; Architecture (Vastu Shastra)